Bioactive starch nanocomposite films with antioxidant activity and enhanced mechanical properties obtained by extrusion followed by thermo-compression. (November 2019) - Estevez-Areco, Santiago; Guz, Lucas; Famá, Lucía; Candal, Roberto; Goyanes, Silvia
Abstract: In this work bioactive starch films with antioxidant activity were developed by extrusion followed by thermo-compression. Rosemary extract was incorporated into starch-glycerol films in different concentrations (2.5%, 5% and 10% w/w with respect to starch). Despite the high mechanical and thermal energy involved during extrusion, rosemary polyphenols remained in the films without losing its activity. Starch nanocomposites were obtained by the incorporation of rosemary nanoparticles, which were formed from the immiscible components of the extract. For low extract concentration, homogeneously dispersed nanoparticles acted as reinforcement of the matrix, increasing stress and strain at break without modifying Young's modulus. At high concentration, the mechanical response was ruled by the miscible components of the extract, which acted as an additional plasticizer. In this case, nanocomposite films with higher values of strain at break and lower values of Young's modulus and stress at break were obtained. All the developed films released a high percentage of polyphenols to hydrophilic, lipophilic or acid food simulants in a short time interval. Experimental release data was fitted by Weibull equation in order to elucidate release mechanisms. According to the results of this research, rosemary extract can be incorporated into starch films by extrusion without previous encapsulation. Despite thermal and mechanical energy involved in the process, the rosemary compounds kept their antioxidant activity and were released from the bioactive films. Graphical abstract: Image 1 Highlights: Bioactive nanocomposite starch films containing rosemary extract were developed by extrusion. Rosemary extract maintained its antioxidant activity after extrusion. Most of rosemary polyphenols were released to several food simulants. Low extract concentration increased stress and strain at break. High concentration lowered Young's modulus and stress at break.